Ecotourism as A Source of Science Learning in Indonesia: A Systematic Literature Review - Annam, Syarful (Yayasan Siti Widhatul Faeha, 2026)
One relevant concept in supporting contextual learning is the use of ecotourism as a learning resource. Ecotourism serves not only as a recreational activity but also as an educational medium that integrates environmental, social, and cultural aspects. This study aims to comprehensively examine the use of ecotourism as a science learning resource in Indonesia through a Systematic Literature Review (SLR) approach. The method follows the PRISMA 2020 guidelines, including identification, screening, eligibility, and inclusion stages. A total of 20 selected articles from the Scopus and SINTA databases, published between 2016 and 2025, were analyzed using content analysis. The findings indicate that ecotourism has significant potential as a resource for contextual and experiential learning. Its implementation has been proven to enhance students’ scientific literacy, critical thinking skills, and pro-environmental attitudes and behaviors. Furthermore, integrating ecotourism into learning supports the implementation of Education for Sustainable Development (ESD) by strengthening ecological awareness and sustainability values. However, the application of ecotourism as a learning resource still faces several challenges, including limited curriculum integration, policy support, and the readiness of educational resources. Therefore, it is necessary to develop systematic, innovative, and technology-based learning models to optimize the use of ecotourism in science education.